Analisis Tingkat Rawan Kekeringan Berbasis Sistem Informasi Geografis di Kecamatan Candipuro Kabupaten Lampung Selatan - Amelia, Ayu; Amin, Muhammad; Ridwan, Ridwan; Asmara, Sandi (abe.fp.unila.ac.id, 2022)
The impact of drought can affect various aspects of life. One that is threatened by the effects of drought is agricultural land and rice fields, which are threatened with failure due to reduced water supply. South Lampung Regency is one of the largest rice producing districts in Lampung Province, with rice fields covering an area of 38,688 ha, South Lampung Regency is capable of producing 321,822 tons of rice. While Candipuro District is the largest producing district in South Lampung Regency with a total rice production of 55,192 tons of rice. From the magnitude of the potential Candipuro District has drought constraints in utilizing the potential of paddy fields optimally. One of the efforts that can be done to anticipate drought is by mapping the rice fields in Candipuro district which is prone to drought. One of the technologies that can be used in mapping is application-shaped technology called GIS (Geographic Information System) Application. The purpose of research on the level of drought based on Geographic Information System in Candipuro District is (1) to obtain a map of the distribution of drought-prone rice fields in Candipuro District, (2) to determine the level of drought-prone rice fields in Candipuro District, (3) to analyze the dominant factors that affect the level of drought-prone rice fields in Candipuro District. The method used in this study is the method of overlap (overlay) and scoring (scoring) with GIS analysts. Overlay and scoring methods were performed on 5 drought parameters, namely rice field irrigation, slope slope, soil texture, soil solum and rainfall. The results of research on rice field drought in Candipuro district obtained two levels of drought prone, namely, medium and high. Paddy land with a classification of medium vulnerability level has an area of 4,050.43 or comparable to 61.8% of the total area of paddy land in Candipuro district, while the classification of high vulnerability level has an area of 2,503. 3 ha or comparable to 38.2% of the total area of paddy land in Candipuro District. Keywords: Drought, Paddy Field, Candipuro District, Geographic Information System